The relationship between eating disorder and stress among dancers in the Faculty of Dance, ASWARA - Siti Zulaikha Mohamad Zaki
Eating disorders are related to unhealthy eating behaviour that put a person's life in danger. This is because eating disorders affect people physically and emotionally. Dancers have high prevalence of risk of eating disorders because they were very concern about their body figure, appearance and fear of gaining weight which can lead to unhealthy dieting habits. Stress is any situation that evokes negative thoughts and feelings in a person. Extreme training and injury are two factors identi fied causing stress among dancers. Many studies abroad show that stress among dancers has led them to eating disorders. This study intended to examine the level of eating disorders, to identify the level of stress, to determine the relationship between eating disorders and stress, to examine the differences of level of eating disorder 11 tween male and female and to identify the differences of level of stress between male and female among the dancers. This study was conducted in Faculty of Dance, among 142 dancers quantitatively. Eating Attitudes Test (EAT-26) and International Stress Management Association UK Stress Questionnaire (ISMA UK) was used to identify the risk of developing eating disorders and the stress level among the dancers. The study found that the level of eating disorders and stress are high among the dancers. The Pearson Correlation Coefficient result showed positive relationship and the strength of the relationship was moderate (r=0.75, p<O.O l). As a conclusion, the finding supports research done by previous researchers abroad as the relationship between eating disorders and stress are also found high among dancers in this study. Eating disorders are prevalent in a sample of dancers and were strongly associated with various psychological, behavioural and socio environmental domains. Future prospective and experimental studies are necessary to advance our understanding of the risk factors in order to enable better preventive programme to be planned.